Evidence-Based Web and Ageing Guidelines - Mughal, Shabana; Zaphiris, Panayiotis (My University, 2003)
This paper presents a set of evidence-based guidelines for designing websites for the elderly. Extensive literature review was conducted, guidelines were developed and supported by literature, and finally the guidelines were used to evaluate ten websites that have as their primary target audience the elderly.